Multidimensional modeling of the economy of forest management and reforestation - Salimova, Guzel; Ableeva, Alisa; Lubova, Tatiana; Sharafutdinov, Aidar; Araslanbaev, Irek (Ecological modelling, 2022)
•Regions are set for the selected clusters.•Clusters with high, medium and low levels have been identified.•Much attention is paid to the reproduction of forest resources. The article presents a study of the system of indicators characterizing the forest industry and the reproduction of forest resources of territories. A hierarchical classification of the subjects of the Volga Federal District of the Russian Federation by indicators characterizing the resource potential of logging regions and organizations, the results of logging organizations, the state of forest resources and environment has been performed. The classification of the system of indicators of timber industry from the position of cluster analysis was first performed. Clusters with high, medium and low levels of forestry development and reforestation have been identified. Regions are set for the selected clusters. The formation of clusters will make it possible to more efficiently use the forest resources of the District, will contribute to interregional cooperation, obtaining a larger total income, combining experience and efforts in the field of forest resources reproduction. Much attention is paid to the reproduction of forest resources. Regions of the Volga Federal District are characterized by better indicators of reforestation, reproduction of forest resources, their safety compared to the value of indicators of the Russian Federation. In the regions of cluster 1, where forest lands occupy a significant share of the area, less grain is produced per capita than in other clusters or average in the District and across Russia. The highest value of grain per capita is produced in the regions of cluster 2. The regions of cluster 3 are characterized by the average level of crop and livestock production per capita, quite developed agriculture. Total contribution of agriculture and forestry to Gross Regional Product in the regions of this cluster is the highest – 9.6%, which exceeds the average level both for the District and for Russia as a whole. The regions of cluster 3 also have the largest share of investments in fixed capital by economic activity ‘Agriculture, forestry and fishing’ in total investments. It is also partly the result of the fact that in this cluster the largest share of intramural current expenditures on R&D on agricultural sciences (6.74% of total intramural current expenditures on R&D). This result confirms the hypotheses put forward about the need for a scientifically grounded approach to the processes of reforestation, agriculture and forestry, attracting investments in fixed capital of this type of economic activity. The formation of clusters will make it possible to more efficiently use the forest resources of the District, will contribute to interregional cooperation, obtaining a larger total income, combining experience and efforts in the field of forest resources reproduction.